2019
DOI: 10.1039/c9ra06243b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel functional ionic liquids and their application in biomass

Abstract: A series of dicationic and monocationic ionic liquids (ILs) were synthesized and investigated and it was found that these functional ILs have important implications in the design of homogeneous and heterogeneous systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…A similar protocol was employed for the preparation of hexafluorophosphate [1-(1-pyridinium-yl-pentyl)-4-methylimidazolium] bromide ([PF 6 ][(PYR)C 5 (MIM)][Br]). 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar protocol was employed for the preparation of hexafluorophosphate [1-(1-pyridinium-yl-pentyl)-4-methylimidazolium] bromide ([PF 6 ][(PYR)C 5 (MIM)][Br]). 11 …”
Section: Methodsmentioning
confidence: 99%
“…Our previous study showed that the miscibility of DILs in water could be altered by the combination of a hydrophobic anion (PF 6 − ) and a hydrophilic anion (Cl − ). 11 However, in current studies, there is very limited information concerning the application of DILs. It is therefore necessary to investigate DILs for the treatment of lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%
“…This is different with P. janthinellum FHH1 and P. oxalicum FLY4, because high hydrolysis efficiency was observed with ILs-pretreated corn stalk. [PF6] at 100 °C, a high reducing sugar yield for corn stalk was achieved at 18.80% (Han et al 2019). The residue was obtained at 68.75% after ILs treatment.…”
Section: Enzymatic Hydrolysis Of Corn Stalkmentioning
confidence: 95%
“…Ionic liquids were synthesized according to Han et al (2019). Pyridine (1.0 mmol) and 1,4-dichlorobutane (1.0 mmol) were reacted at 60 °C for 4 days.…”
Section: Synthesis Of Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation